“They don´t represent us!” Opportunities for a Social Movement Unionism Strategy in Spain - Köhler, Holm-Detlev; Calleja Jiménez, José (Relations industrielles / Industrial Relations, 2015)
Our goal is to analyze strategies of union revitalization that have been successful elsewhere and have the potential to become so in Spain. Within these practices, Social Movement Unionism focuses on alliances with other groups to improve unions’ social efficiency. In this article, we address the applicability of the principles of Social Movement Unionism in the specific case of Spain. Given the transformations in the Spanish economy and labour laws tending towards further deregulation, Spanish unions have had to react. The emergence of new social movements such as the Indignados or Mareas Ciudadanas (civic tides) and the declining confidence in unions among the Spanish population, make this approach timely and appropriate.For this article, we will take certain aspects from the trade union revitalization debate and combine them with the main theories on New Social Movements. We will apply these approaches to a specific case study: The viability of cooperation between the largest Spanish trade unions and the recent social movements arising from the Indignados movement. For this purpose, we will primarily use data from secondary sources and transcripts of interviews conducted with unionists and social movement activists. With all these elements taken into consideration, we will conclude by showing the inhibiting and facilitating conditions for the development of a Social Movement Unionism strategy for the referred actors.